Knowledge modelling for an Intelligent Tutoring System (ITS) domain : Precalculus - Hashim, Rathiah; Ahmad, Abd. Manan; Mohamed Yunus, Mohd. Radzi (2000)
This paper presents a knowledge model (KM) of an ITS with Precalculus as the domain knowledge. The Knowledge Model is represented by Semantic Net, organized as interconnected knowledge entities in the form of nodes. The comprehensiveness of the knowledge domain depends largely on the richness of the interconnectivity of nodes. A working prototype, built using an object oriented paradigm, exists that shows the correctness and feasibility of this model. Any standard Java compatible World Wide Web (WWW) browser with be able to access the knowledge model witb a simple Graphical User Interface (GUI) to view the content of its structure.